The picture exchange communication system and adults lacking functional communication: A research review. Issue 1 (2nd January 2021) - Hughes-Lika, Jamie; Chiesa, Mecca
ABSTRACT: PECS training for children with Autism Spectrum Disorder and Intellectual Disabilities has been extensively evaluated. In contrast, there is a dearth of literature on outcomes of PECS training for adults lacking functional communication skills. A literature search produced five empirical studies involving PECS training with 18 adults. The participants involved presented with a wider range of intellectual and physical challenges than those typically found in child-related research. Where noted, severity of diagnoses ranged from mild to profound and included participants with single, dual and triple diagnoses, the majority with dual diagnoses. Each of the studies shows results in line with child-related research. While the amount of research is limited, the outcomes of these few studies are profound in their implications for adults with a variety of intellectual disabilities and physical challenges. Implications for both children and adults are considered.